Pengaruh Fintech terhadap perilaku konsumtif Gen Z pada siswa SMA Triguna 1956 Jakarta - Siti Hindun; Aprillia Fransiska; Saskya Azzahra; Yeni Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The development of financial technology (fintech) has brought significant changes to people's financial transaction patterns, particularly among Generation Z, who have a high level of digital technology usage. Easy access to various fintech services, such as digital wallets and cashless payments, has the potential to encourage consumer behavior if not balanced with adequate financial literacy. This Community Service activity aims to improve students' understanding of fintech and its impact on consumer behavior at SMK Triguna 1956 Jakarta, while also raising awareness of the importance of wise financial management. The activity's implementation methods included counseling, educational material presentations, interactive discussions, and evaluation of participants' understanding. The results of the activity indicate an increase in students' knowledge about the types of fintech, their benefits and risks, as well as a change in more critical attitudes toward consumer behavior in the use of digital financial services. This activity is expected to make a positive contribution to shaping more responsible financial behavior among Generation Z and support the improvement of financial literacy in the school environment. Keywords: financial technology, consumer behavior, Generation Z, community service, financial literacy